25. INVESTIGATING THE INCIDENCE OF HYPOTHERMIA IN ELDERLY PATIENTS UNDERGOING TRANSURETHRAL RESECTION OF THE PROSTATE (Vietnam Journal of Community Medicine, 2024)
Objective: To investigate the incidences, severity, and early consequences of hypothermia in elderly patients undergoing transurethral resection of the prostate.Subject and method: Cross-sectional study. Patients ≥ 65 years old receive spinal anesthesia for transurethral resection of the prostate. Prevention methods of perioperative hypothermia by keeping warm before and after surgery with cotton blankets, using warm intravenous fluids during surgery. Tympanic temperatures were measured at 30 minutes intervals after spinal anesthesia. Intra and post-operative shivering were also assessed.Results: 80 patients, average age 74 ± 7 years were included in the study. The incidence of hypothermia in elderly patients undergoing transurethral resection of the prostate was 68.8%. Of these, mild hypothermia was 65%, moderate hypothermia was 3.8%, and there were no patients with severe hypothermia. The incidence of intra- and post-operative shivering was 20%.Conclusion: The incidence of perioperative hypothermia in elderly patients undergoing transurethral resection of the prostate was high. More attention should be paid to temperature monitoring and prevention methods of hypothermia.
Keywords: Perioperative hypothermia; transurethral resection of the prostate (TURP); warm intravenous fluids